2019
DOI: 10.3390/toxins11010032
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a Broadly Cross-Neutralizing Antibody Fragment against Several Mexican Scorpion Venoms

Abstract: The recombinant antibody fragments generated against the toxic components of scorpion venoms are considered a promising alternative for obtaining new antivenoms for therapy. Using directed evolution and site-directed mutagenesis, it was possible to generate a human single-chain antibody fragment with a broad cross-reactivity that retained recognition for its original antigen. This variant is the first antibody fragment that neutralizes the effect of an estimated 13 neurotoxins present in the venom of nine spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 35 publications
2
28
0
Order By: Relevance
“…These approved therapies all fall within the areas of bacterial and viral infections [1,8]. In contrast, the development of therapeutic monoclonal antibodies against parasitic diseases, animal envenomings, and mushroom poisonings is far behind, although recent reports within trypanosomiasis therapy and recombinant antivenoms against snakebite and scorpion envenoming demonstrate potential and utility of employing antibody technologies in these fields [9,93,95]. The reason for the disparity in the development stages between these two groups (bacterial and viral infectious diseases vs. parasitic diseases, animal envenomings, and mushroom poisonings) may possibly be found in their potential for causing uncontainable epidemic outbreaks coupled to the limited commercial prospects that may exist for the latter group of diseases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These approved therapies all fall within the areas of bacterial and viral infections [1,8]. In contrast, the development of therapeutic monoclonal antibodies against parasitic diseases, animal envenomings, and mushroom poisonings is far behind, although recent reports within trypanosomiasis therapy and recombinant antivenoms against snakebite and scorpion envenoming demonstrate potential and utility of employing antibody technologies in these fields [9,93,95]. The reason for the disparity in the development stages between these two groups (bacterial and viral infectious diseases vs. parasitic diseases, animal envenomings, and mushroom poisonings) may possibly be found in their potential for causing uncontainable epidemic outbreaks coupled to the limited commercial prospects that may exist for the latter group of diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Here, it was demonstrated that phage display selection employing naïve human antibody libraries could be exploited to discover mixtures of human monoclonal IgGs that could abrogate dendrotoxin-mediated neurotoxicity of black mamba (Dendroaspis polylepis) whole venom in vivo [93]. Also, other researchers have recently reported the discovery of human monoclonal scFvs that can broadly neutralize toxins from multiple scorpion species [94,95], as well as it has been shown that experimental antivenoms based on nanobodies and nanobody-constructs can be used to effectively neutralize snake toxins and venoms [96,97]. These and other recent results in antibody discovery within animal envenomings [90,98] ( Figure 4) now warrant further development efforts within envenoming therapy.…”
Section: Envenoming By Animal Bites and Stingsmentioning
confidence: 99%
“…The gene was mutated in selected residues of the CDR3 region, where upon a new antibody library was constructed and used to select binders against other toxins from C. noxius , as well as other scorpions. A resulting scFv displayed neutralizing abilities against 13 neurotoxins present in the venoms of nine different species of Mexican scorpions (145).…”
Section: Advances In Antivenom Researchmentioning
confidence: 99%
“…Currently, we have two neutralizing antibody fragments derived from the parental scFvs 3F and C1, isolated by phage display procedures from a non-immune human library and using Cn2 toxin from the venom of the scorpion Centruroides noxius [ 10 ]. They were obtained by means of several cycles of directed evolution to increase their affinity toward Cn2 toxin as well as their cross-neutralization against different toxins from Mexican scorpion venoms, such as Css2 (from C. suffusus ), Cll1 and Cll2 (from C. limpidus ), and Ct1a (from C. tecomanus ) [ 11 ]. In this way, scFv LR was generated, which is capable of neutralizing Cn2 and Css2 toxins [ 12 ] as well as the corresponding whole venoms.…”
Section: Introductionmentioning
confidence: 99%